Experiences of rural women with damages resulting from an earthquake in Iran: a qualitative study - Javad Yoosefi Lebni; Farhad Khorami; Farbod Ebadi Fard Azar; Bahar Khosravi; Hossein Safari; Arash Ziapour (BMC Public Health, 2020)
Abstract Background Women, with more vulnerabilities and less access to resources, are often seen as victims of natural disasters. Therefore, the present study aimed to investigate the experiences of rural women with damages resulting from an earthquake in Iran. Methods In this research, a qualitative approach, as well as the conventional content analysis was employed. The study population consisted of rural women residing in the earthquake-stricken areas of Sarpol-e Zahab and Salas-e Babajani counties in Kermanshah Province, Iran. Semi-structured interviews were used for data collection. Moreover, sampling was purposeful, theoretical saturation was achieved by conducting 22 interviews, and the data analysis process was performed according to the steps proposed by Graneheim and Lundman. For the strength and transferability of the research, Lincoln and Guba’s Evaluative Criteria were used. Results There were seven categories regarding the experiences of rural women after the earthquakes including neglecting the health needs; tension in the family and marital relations; gender inequality in the provision of assistance; feeling insecure; ignoring the ruling culture of the region; concealing needs for fear of stigmatization, and incoherent mourning as well as two categories regarding their reactions to and interaction with the earthquake consequences including positive and negative interactions. Conclusions Paying more attention to the needs of rural women, taking the culture governing the village into account at the time of service delivery, and helping them with positive adaptations are some indispensable measures that should be taken.